RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND MOTIVATION WITH WITH EMPLOYEE JOB PERFORMANCE AT KPU BOGOR CITY AND BOGOR REGENCY - Ratno . (STIE Binaniaga, 2018)
The purpose of this study is to determine whether there is a relationship between transformational leadership and work motivation with employee job performance partially and simultaneously. The population of this study is all employees at KPU Bogor City, Bogor Regency and Cianjur regency which is 80 employees. The sampling technique using the census is all the population used for research data. So the number of samples taken in this study as many as 80 respondents who are employees at KPU Bogor, Bogor and Cianjur.The research instrument is the questionnaire. The collected data is then processed using correlation analysis techniques with the help of SPSS (Statistical Package for Social Science) software. The results showed that: Firstly, transformational leadership has a positive relationship with employee’s job performance with a value of 0.652, this relationship fall into the category of strong relationships. While the influence of transformational leadership on employee job performance of is 42.5%. Secondly, work motivation has a positive relationship with employee job performance with a value of 0.892, this relationship is categorized very strong relationships. While the influence of work motivation on employee job performance is 79,5%. Thirdly, transformational leadership (X1) and work motivation (X2) simultaneously have a positive relationship with employee job performance (Y) of 0, 0.894, this relationship shows a very strong relationship between transformational leadership variable and work motivation simultaneously with employee job performance variable . Influence of transformational leadership (X1) and work motivation (X2) simultaneously has affected employee job performance (Y) of 80,0%. Keywords: Transformational Leadership, Work Motivation and Employee Performance